Reflection through blogs in ESL project-based learning - Hon, Isode Pei Sha (2018)
Reflective learning (RL) and project-based learning (PBL) have long been acknowledged as important aspects of personal and professional development. Yet, the practice of RL and PBL in Malaysian classrooms are still underutilized and students are not getting sufficient input to meet the demands of the international standards, as reported in the 12 OECD, PISA 2012 Database. To address this, the Malaysian Ministry of Education has produced the Project-Based Learning Handbook (2006) and accompanied by the new Malaysia Education Blueprint (2013 - 2025) which contain necessary information and guidelines to produce students who can keep pace in an increasingly competitive global economy. However, an inductive and reflective research to discover and describe the Malaysian students’ perception and experience of both RL and PBL combined has yet to be conducted. The aim of this study is to identify the dimensions and frequency of reflections found in the learners’ blogs, the extent learners include stages of Gibbs Reflective Cycle in their reflections through blogs, and the extent learners identify with reflective learning and collaborative learning through their projects. The sampling for the study was purposeful and the participants were 10 TESL, 3rd year undergraduates. Research data was collected from participants’ reflections through blog entries and from follow-up qualitative interviews. In this study, data analysis also included the transcribing and reading of blog entries and interviews. The findings of the study showed that participants were engaged in reflection and produced responses that included all three reflection dimensions within their personal and group blogs. More reflective writing was produced using the initial stages of reflection rather than those which required higher order thinking skills. Thus, there were more reflections on descriptions of their experience and the feelings that they had developed in the process of completing their project. Furthermore, reflective learning and collaborative learning were evidently present throughout this project. Participants also suggested the significance of conflict-resolution as an essential element that emerges every time they had to overcome obstacles in the process. This study provides valuable information on how students perceive and experience RL and PBL which are crucial to better equip our students holistically to allow them to succeed in the 21st century.